Antimicrobial activities of some marine actinonycetes isolated from Malaysians waters - Zainal Abidin, Zaima Azira; Ahmad, Asmat; Usup, Gires (2009)
Marine actinobacteria were isolated from sediment and water samples from Malaysian waters using starch-yeast extract agar with seawater and marine agar (Difco) as a selective medium to isolate the actinomycetes. Ten isolates were selected from a collection of 300 isolates for further investigations based on colony morphology and pigment production. Genomic DNA from these isolates were extracted and subjected to polymerase chain reaction (PCR) to detect the presence of polyketide synthase type I (PKS-I) and non-ribosomal peptide syntethases (NRPS) [1]. Molecular identification was also performed using 16S rRNA gene partial sequencing. A phylogenetic tree based on 16S rRNA gene sequences was constructed using MEGA version 4 [2]. Scanning electron microscopy (SEM) was also performed on these isolates. Evaluation of antimicrobial activity was performed for isolates that exhibited the presence of both PKS-I and NRPS genes, and NRPS gene only. These isolates were challenged against of 5 Gram negative bacteria - E.coli, P. vulgaris, P. aeruginosa, P. mirabilis and S. marcescens; 3 Gram positive bacteria – Methicillin-resistant S. aureus (MRSA), B.subtilis and S. aureus; and 3 fungi - Candida parapsilosis, A. niger and Candida albican. The antimicrobial test was conducted by placing the isolates on trypticase soy agar (TSA) which had been inoculated with the test organisms. The antimicrobial activity was determined as a clear zone of inhibition surrounding the isolate. Eight isolates exhibited the presence of both PKS-I and NRPS genes of which 5 isolates belong to the genus Streptomyces, while another 2 isolates displayed only NRPS gene. Five isolates, mostly Streptomyces species demonstrated high antimicrobial activity against most of the test organisms which could be related to the presence of PKS-I and NRPS genes. Streptomycetes produce approximately 75% of commercially and medically useful antibiotics worldwide [3] therefore, it was anticipated that the Streptomycetes isolates in this study would display high antimicrobial activities. However, 2 isolates displayed no antimicrobial activity at all even though both genes were detected in them. Based on 16S rRNA gene sequencing, these isolates were presumed to belong to the genus Rhodococcus and Pseudonocardia. The presence PKS-I and NRPS genes might not necessarily result in antimicrobial activities since the function of polyketides is not confined to antimicrobial activities but may have other useful properties such as antihelmintics, anticancer or immunosuppressive agents [4].Nevertheless, early evaluation of these isolates based on the presence of both genes would allow to focus the screening of isolates that possessed high metabolic potential. In conclusion, Malaysian waters have the potential as important natural resources for exploration of marine actinomycetes that possess the ability to produce a relatively high rate of new antimicrobial bioactive agents.